2020
DOI: 10.1096/fj.201802061rr
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase inhibitors and interferon‐α increase tunneling nanotube (TNT) formation and cell adhesion in chronic myeloid leukemia (CML) cell lines

Abstract: Chronic myeloid leukemia (CML) is a stem cell disease of the bone marrow where mechanisms of inter‐leukemic communication and cell‐to‐cell interactions are proposed to be important for optimal therapy response. Tunneling nanotubes (TNTs) are novel intercellular communication structures transporting different cargos with potential implications in therapy resistance. Here, we have investigated TNTs in CML cells and following treatment with the highly effective CML therapeutics tyrosine kinase inhibitors (TKIs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 100 publications
(223 reference statements)
0
9
0
Order By: Relevance
“…The fact that the administration of imatinib did not cause an increase in TNT formation in BCR-ABL1 cells presenting Ba/F3, but rather in Ba/F3 cells alone, indicates that the increase in TNT most likely involves other elements besides the inhibition of BCR-ABL1. This was also demonstrated by the evaluation of intracellular signaling through mass cytometry, in which known BCR-ABL1 targets, such as phospho-STAT-5, were reduced by TKI administration, regardless of the reported differences in TNT response [155].…”
Section: Tnts and Chronic Myeloid Leukemia (Cml)mentioning
confidence: 86%
See 1 more Smart Citation
“…The fact that the administration of imatinib did not cause an increase in TNT formation in BCR-ABL1 cells presenting Ba/F3, but rather in Ba/F3 cells alone, indicates that the increase in TNT most likely involves other elements besides the inhibition of BCR-ABL1. This was also demonstrated by the evaluation of intracellular signaling through mass cytometry, in which known BCR-ABL1 targets, such as phospho-STAT-5, were reduced by TKI administration, regardless of the reported differences in TNT response [155].…”
Section: Tnts and Chronic Myeloid Leukemia (Cml)mentioning
confidence: 86%
“…A different study evaluated TNTs in CML cells after the administration of tyrosine kinase inhibitors (TKIs) and interferon-α (IFNα) [155]. It was demonstrated that CML cells from patients in chronic phase or from blast crisis phase cell lines, Kcl-22 and K562, generated scarce or no TNTs.…”
Section: Tnts and Chronic Myeloid Leukemia (Cml)mentioning
confidence: 99%
“…Coculture of leukemic cells with MSCs is associated with actin polymerization (71,82) and consequent cytoskeletal remodeling in CLL cells. For other leukemias such as chronic myeloid leukemia (83,84) and acute lymphoblastic leukemia (85)(86)(87), tunneling nanotubes have been identified as a novel mode of intercellular crosstalk. Tunneling nanotubes are long and thin membranous structures that allow the exchange of material [such as mitochondria (85), vesicles or proteins (83)] between leukemic cells and stromal cells.…”
Section: Direct Contact: Cll/stroma Coculture Homing and Adhesion Mmentioning
confidence: 99%
“…The exchange of misfolded proteins and damaged genetic material through TNTs in cancers is considered one of the major phenomena that contribute to the transformation of healthy cells into tumoral cells and increases in metastasis formation [5,27]. While TNTs have been linked to communication and spreading in several types of cancer [28], such as prostate [29], bladder [30][31][32], pancreatic [33], and breast cancer [34], as well as different types of leukemia [35][36][37]. Glioblastoma multiforme (GBM) is by far the most studied for the consequences of TNT activity [4,38].…”
Section: Tunneling Nanotubes 1what Are Tunneling Nanotubes?mentioning
confidence: 99%